The antimicrobial interactions of Agathosma crenulata, Dodonaea viscosa and Eucalyptus globulus combination and their chemical profiling - Zonyane, Samkele (Stellenbosch : Stellenbosch University, 2013)
Thesis (MSc)--Stellenbosch University, 2013.